Contrasted ecological niches shape fungal and prokaryotic community structure in mangroves sediments. (19th March 2019) - Luis, Patricia; Saint‐Genis, Geoffroy; Vallon, Laurent; Bourgeois, Carine; Bruto, Maxime; Marchand, Cyril; Record, Eric; Hugoni, Mylène
Summary: Mangroves are forest ecosystems located at the interface between land and sea where sediments presented a variety of contrasted environmental conditions (i.e. oxic/anoxic, non‐sulfidic/sulfidic, organic matter content) providing an ideal ecosystem to study microbial communities with niche differentiation and distinct community structures. In this work, prokaryotic and fungal compositions were investigated during both wet and dry seasons in New Caledonian mangrove sediments, from the surface to deeper horizons under the two most common tree species in this region ( Avicennia marina and Rhizophora stylosa), using high‐throughput sequencing. Our results showed that Bacteria and Archaea communities were mainly shaped by sediment depth while the fungal community was almost evenly distributed according to sediment depth, vegetation cover and season. A detailed analysis of prokaryotic and fungal phyla showed a dominance of Ascomycota over Basidiomycota whatever the compartment, while there was a clear shift in prokaryotic composition. Some prokaryotic phyla were enriched in surface layers such as Proteobacteria, Euryarchaeota while others were mostly associated with deeper layers as Chloroflexi, Bathyarchaeota, Aminicenantes . Our results highlight the importance of considering fungal and prokaryotic counterparts for a better understanding of the microbial succession involved in plant organic matter decomposition in tropical coastal sediments.